(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
Feed is an important component in aquaculture because the availability of feed will affect the growth and survival of fish. This study aims to utilize protein-rich chicken intestine as an alternative feed to obtain optimal growth for catfish. Fish maintenance was carried out for 60 days by feeding 10% of body weight and given once a day. The results showed that feeding catfish by utilizing chicken intestine waste can provide optimal growth. The absolute weight gain was 103.84 g, the absolute length was 28.13 cm, the specific growth rate (SGR) was 4.65% per day, and the survival rate was 85%.